Many alternative classification of air situations where the density probability distribution are known accurately - Остроумов, І.В.; Кукуш, О.Г.; Харченко, В.П. (Proceedings of National Aviation University (archive), 2007)
A method for identification class of air situation is proposed. Also this article represents the algorithm for calculating probability of correct selection by Bayes formula when the frequency distribution is known roughly. This method is raising accuracy of identification of air situation classes and makes it possible to avoid the conflict situation earlier.